Health Service Executive December 2012 performance report. National Service Plan 2012. (Health Service Executive, 2013)
The Performance Report (PR) provides an overall analysis of key performance data from Finance, HR, Hospital and Primary & Community Services. The activity data reported is based on Performance Activity and Key Performance Indicators outlined in the National Service Plan 2012. The Social Inclusion section gives figures for the total number of clients in methadone treatment each month. (p.27) In December 2012, the total number of clients in methadone treatment in December was 9,470 of this 93.9% were outside prisons and 6.1% (581) were in prisons. Of the 8,889 persons who are on methadone outside prison, the regional breakdown is as follows; • HSE DML – 5,017 • HSE DNE – 3,038 • HSE South – 489 • HSE West – 345 A Supplementary Report is also produced each month which provides more detailed data on the metrics covered in the Performance Report. See page 45 and page 58 for details of those in methadone treatment and expenditure.